The Calculation of The Need for Medical Record Personel Based on The Full-Time Equivalent Method in The Outpatient Registration Department of Public Health Center - Sapto Adi; Dian Mawarni; Siti Istiqomah (Jurnal Kesehatan Prima, 2021)
Public health center X is one of the public health center with high outpatient loads in Malang City. On average, the daily amount of outpatients is 119. The high load of outpatient directly affects employee’s working load. One of the units considered susceptible to working load increase is the medical record unit at the registration department because they have to interact with all visiting patients. The study aimed to discover the need for medical record personnel at the outpatient registration department of public health center X using the Full-Time Equivalent (FTE) method. The study used a descriptive study design and a quantitative approach. The researchers utilized a total sampling technique with two medical record personnel at the outpatient registration department. The study instrument employed was the outpatient registration daily log of Public health center X. The study results show that the working load of medical record personnel at the BPJS patient registration department had an FTE index value of 2.24 > 1.28, categorized as overload. Meanwhile, medical record personnel at the non-BPJS patient registration department had an FTE index value of 0.96 < 0.99, categorized as underload. Therefore, it can be concluded that Public health center X requires two additional medical record personnel at the BPJS patient registration department, while the non-BPJS patient registration department did not require additional medical record personnel.